2020
DOI: 10.1186/s40942-020-00216-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative optical coherence tomographic findings in patients undergoing subretinal gene therapy surgery

Abstract: Background: To analyze intraoperative OCT (iOCT) findings during subretinal gene therapy. Methods: A single-center, retrospective, observational, case series study of twenty one eyes submitted to subretinal gene therapy. Intrasurgical high definition videos were included for analyzes. Cases with absence of iOCT video or unsuccessful bleb creation were excluded. Sharp needle tip (SNT) or blunted needle tip (BNT) and their interaction with neurosensory retina were evaluated. Presence of subretinal air bubbles, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…Vitreoretinal surgeons well versed in subretinal gene therapy have reported the utility of intraoperative optical coherence tomography (OCT), allowing in vivo real-time feedback during surgical cases. 97 The creation of the subretinal bleb with a microneedle (typically a 38- to 41-gauge, Teflon-tipped, either extendable or nonextendable, cannula that is placed through a pars plana trocar) is a challenging and critical step in the procedure. 98 The needle-penetration step has a narrow margin of error: excessively deep penetration of the needle tip can result in hemorrhage, cannula tip obstruction, unintentional suprachoroidal delivery of vector, or permanent RPE injury; however, too shallow needle penetration can create retinoschisis by intraretinal hydration during bleb formation.…”
Section: Main Textmentioning
confidence: 99%
“…Vitreoretinal surgeons well versed in subretinal gene therapy have reported the utility of intraoperative optical coherence tomography (OCT), allowing in vivo real-time feedback during surgical cases. 97 The creation of the subretinal bleb with a microneedle (typically a 38- to 41-gauge, Teflon-tipped, either extendable or nonextendable, cannula that is placed through a pars plana trocar) is a challenging and critical step in the procedure. 98 The needle-penetration step has a narrow margin of error: excessively deep penetration of the needle tip can result in hemorrhage, cannula tip obstruction, unintentional suprachoroidal delivery of vector, or permanent RPE injury; however, too shallow needle penetration can create retinoschisis by intraretinal hydration during bleb formation.…”
Section: Main Textmentioning
confidence: 99%
“…However, during subretinal injection, reflux from the subretinal bleb into the vitreous humor can occur and may be a factor contributing to the development of vitritis in some eyes. 24 , 25 A vitrectomy is performed before subretinal injection in human and NHP studies and this step cannot be replicated in the mouse model; however, understanding the immune response to AAV therapies that escape the subretinal space will help to clarify the importance of this variable on patient outcomes. Among the clinical trials utilizing an intravitreal approach, the ongoing X-linked retinoschisis trial (NCT02317887) found dose-related inflammation in multiple subjects as well as a dose-related increase in serum AAV8 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…After OCT imaging, the animal was euthanized and both right (injected) and left (fellow, uninjected) eyes were enucleated and intraocular contents collected separately as described by John et al 14 Briefly, each eye was rinsed in a flow buffer, placed in 50 μL of flow buffer, the cornea and lens removed, and the aqueous humor, iris, vitreous, retina, and retinal pigmented epithelium were collected. The intraocular contents were incubated with 10 mg/mL of DNAse (Roche, Germany) and 0.5 mg/mL of collagenase (Roche, Germany) at 37°C for 25 [30-F11, 565967]) for 30 minutes at 4°C. After staining, cells were washed and fixed with 1% paraformaldehyde in PBS.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Of course, SRI is a delicate procedure, requiring a vitrectomy, retinotomy, and the development of a transitory iatrogenic neuroretinal displacement and it is potentially associated with a number of complications, including retinal tears, cataract progression, or retinal/choroidal hemorrhages. With respect to SRI, vitreoretinal subspecialists have reported the utility of in vivo real-time monitor of the surgical act through integrated optical coherence tomography (OCT) operating microscope (33).…”
Section: Administration Routesmentioning
confidence: 99%